My cat looks like my dad - Lam, Thao (Owlkids Books, 2019)
"A narrator describes all the ways in which her cat and father are--or are not--alike. They both love milk (we see them with milk mustaches) and sardines (ew!). They both start their mornings with stretches (yoga routine) and their afternoons with naps. What starts out as a humorous series of comparisons and visual gags takes a more meaningful turn when we realize the narrator may not be much like her parents at all. In the end, the narrator proclaims, "My cat is like my dad. But me? I'm like my mom." We see the same blue eyes, the same poofy hair--and then two pairs of dancing feet, but one belongs to a bird! It turns out the narrator is a pet parrot that readers will have glimpsed in the earlier spreads. Family, writes Thao, is what you make it. This is Thao's first picture book with text. Illustrations will still be done in cut-paper collage."--